Digital Marketing Implementation and The Impact on Micro and Small Enterprises (MSEs) Agribusiness Performance in Indonesia - Ratih Septiyanti; Nia Rosiana; Maryono Maryono (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
The micro and small enterprises (MSEs) in the agribusiness sector still face marketing challenges. Digital marketing has the potential to be a marketing solution, but only 33.8 percent of agribusiness MSEs have utilized it in their operations. This study aims to analyse the factors influencing digital marketing implementation by non-food agribusiness micro and small enterprises (MSEs) and evaluate their impact on business performance. The analytical methods used are logistic regression to identify the determinants of digital marketing, and Propensity Score Matching (PSM) to measure its impact on profit, turnover, and market reach. The results show that innovation, education level, labor, business status, and marketing training have a positive and significant influence on digital marketing decisions. Meanwhile, the age of the entrepreneur and business age have a negative and significant influence. Digital marketing has been proven to have a positive impact on market reach. These findings indicate that digital marketing plays a significant role in strengthening the performance of non-food agribusiness MSEs in expanding market access.